Analysis Of The Total Protein Content In Soybean Grain - Jaynaqov Mirzoxid Sharabutdinovich; Gulomidinov Azamatjon Sherzodbek ugli (Peerian Journals Publishing, 2025)
This article examines the total protein content in the grains of certain soybean varieties, with laboratory experiments on protein content conducted at the laboratory of the Institute of Bioorganic Chemistry of the Academy of Sciences of the Republic of Uzbekistan. Local and foreign soybean varieties, selected as the research object, were grown in an experimental field located in the Asaka district of Andijan region. Agrotechnical measures specified in the description of each variety were implemented during cultivation. The protein content indicators of the varieties were compared and discussed based on data provided in scientific literature.
Keywords: soybean; variety; nitrogen; total protein